2004
DOI: 10.1002/lt.20289
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following liver transplantation for seronegative acute liver failure: Experience during a 12-year period with more than 100 patients

Abstract: Seronegative hepatitis is a common cause of acute liver failure (ALF) requiring liver transplantation. The primary aim of this study was to examine outcomes following transplantation in this group and to identify factors associated with early (<2 months) mortality. Patients studied were 110 consecutive cases of seronegative ALF transplanted at the Queen Elizabeth Hospital, Birmingham, between January 1992 and January 2004. Univariate analysis of 44 pretransplantation recipient, donor, and operative variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 21 publications
4
68
0
Order By: Relevance
“…17,18 Nonetheless, the presence of autoantibodies in patients with FHF remains of clinical interest, because many of these patients demonstrate features associated with autoimmunity such as female sex and the presence of human leukocyte antigen DR3 allotype. 19,20 Although there is indeed some overlap between our FHF cohort and that evaluated by Bernal et al, this equated to only nine cases or 13% of the total (W. Bernal, personal communication). Importantly, in our series, the simplified IAIHG criteria appear less sensitive than the "gold standard" of the 1999 criteria, in ascribing an overall (probable or definite) diagnosis of AIH (24% versus 40%).…”
Section: Discussionmentioning
confidence: 75%
“…17,18 Nonetheless, the presence of autoantibodies in patients with FHF remains of clinical interest, because many of these patients demonstrate features associated with autoimmunity such as female sex and the presence of human leukocyte antigen DR3 allotype. 19,20 Although there is indeed some overlap between our FHF cohort and that evaluated by Bernal et al, this equated to only nine cases or 13% of the total (W. Bernal, personal communication). Importantly, in our series, the simplified IAIHG criteria appear less sensitive than the "gold standard" of the 1999 criteria, in ascribing an overall (probable or definite) diagnosis of AIH (24% versus 40%).…”
Section: Discussionmentioning
confidence: 75%
“…The majority (88%) of these latter ALF patients met King's College transplant criteria (see below), reflecting the low likelihood of spontaneous recovery (Wigg et al, 2005). A recent study from the UK suggested that OLT is a more favorable approach to managing patients with non-APAP induced ALF compared to patients with APAP induced ALF.…”
Section: Etiologymentioning
confidence: 99%
“…Graft steatosis, reduced graft size, and ABO-incompatible grafts have all been shown in multivariate analyses to lead to decreased patient and graft survival (Bernal et al, 1998;Bismuth et al, 1995). On multivariate analysis of data from the United Kingdom, the strongest predictor of early mortality in seronegative ALF was higher donor body mass index (BMI), which may be a marker for donor graft steatosis (Wigg et al, 2005). This group found an odds ratio (OR) of 1.2 for every unit increase in donor BMI relative to a normal donor (BMI 25 kg/m2).…”
Section: Survival With Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, even in those patients that fulfill the required transplantation criteria, 3 more than 20% will die in 1 year after LT, and half of the patients will succumb in the next 10 years. 4 In this sense, interventions intended to restrict organ damage may stop or prevent the progression to liver failure, allowing the recovery of organ function, which may ultimately reduce the necessity of liver transplants.…”
mentioning
confidence: 99%